A Comparative Study of Students’ Listening Skills Using Media; Song and Podcast - Siti Nurhaliza; Reflinda Reflinda; Melyann Melani; Eliza Eliza (Modality Journal: International Journal of Linguistics and Literature, 2023)
AbstractListening skill is commonly used in daily activities. Nevertheless, there are a lot of students who still got difficulties when it comes to listening activity. One of the solution to solve listening problem is to use the existance of media, namely song and podcast to help students improving their listening comprehension. In this paper, researcher employed quantitative method with quasi-experimental design using two-group pretest-posttest. The aim of this research were: (1) to find out whether there was a significant difference in achievement of students’ listening skills after being taught by using song and those who were taught by using podcast, and (2) to find out which media that gave more significant effect in students’ listening skills. The data was analyzed by using Independent Sample t-test in SPSS 20. This paper showed that there was significant difference in achievement of students’ listening skills between the students who were taught by using song and those who were taught by using podcast. From the results of the data, teaching listening through podcast gave more significant effect to increase students’ listening skills.Keywords: song, podcast, listening skillsAbstrak  Keterampilan mendengarkan selalu digunakan dalam kegiatan sehari-hari. Meskipun demikian, masih banyak siswa yang mengalami kesulitan dalam kegiatan mendengarkan. Salah satu solusi untuk memecahkan masalah mendengarkan adalah dengan menggunakan media, yaitu lagu dan podcast untuk membantu siswa meningkatkan pemahaman mendengarkan mereka. Dalam penelitian ini peneliti menggunakan metode kuantitatif dengan desain eksperimen semu dengan membandingkan menggunakan two-group pretest-posttest. Tujuan dari penelitian ini adalah: (1) untuk mengetahui apakah ada perbedaan yang signifikan dalam pencapaian keterampilan mendengarkan siswa setelah diajar dengan menggunakan lagu dan mereka yang diajar dengan menggunakan podcast, dan (2) untuk mengetahui media apa yang memberikan pengaruh yang lebih signifikan dalam keterampilan mendengarkan siswa. Data dianalisis dengan menggunakan Independent Sample t-test di SPSS 20. Penelitian ini menunjukkan bahwa ada perbedaan yang signifikan dalam pencapaian keterampilan mendengarkan siswa antara siswa yang diajar dengan menggunakan lagu dan mereka yang diajar dengan menggunakan podcast. Dari hasil data tersebut, kegiatan mendengarkan melalui podcast memberikan pengaruh yang lebih signifikan terhadap peningkatan keterampilan mendengarkan siswa.Kata Kunci: lagu, podcast, kemampuan mendengar